Down-regulation of ESRP2 inhibits breast cancer cell proliferation via inhibiting cyclinD1 - Caiping He; Yuting Chen; Ximin Zhang; Huancun Feng; Yuzhen Rao; Tangyang Ji; Wenya Wang (Scientific Reports)
Abstract Epithelial splicing regulatory protein 2 (ESRP2),an important alternative splicing protein of mRNA, is reported to have a dual role in tumors, which can promote or inhibit the occurrence and development of tumors. However, the function and mechanism of ESRP2 in breast cancer (BC) remain unclear. The distribution of ESRP2 expression in breast cancer and the correlation between ESRP2 expression and the overall survival rate were detected by The Cancer Genome Atlas (TCGA) database. Gene Ontology(GO)analysis, containing biological process, cellular components, and molecular function, was utilized to evaluate the potential mechanism of ESRP2 in breast cancer. The ESRP2 expression in breast cancer cell lines was detected by real-time quantitative PCR analysis (RT-qPCR) and western blotting. Cell clone was performed to examine the proliferation of ESRP2 knockdown in MCF-7 cells. The cell cycle was measured by flow cytometry assays. The role of ESRP2 knockdown in synergistic effect with chemotherapeutic agents was also determined by MTT assay. Bioinformatics analysis demonstrated that the ESRP2 gene was elevated in breast cancer cells and its overexpression was strongly correlated with shorter overall survival. GO analysis revealed that ESRP2 expression was related to cell proliferation. ESRP2 mRNA and protein expression were elevated in breast cancer cell lines, compared to the normal human breast cell line MCF-10 A. Dwon-regulation of ESRP2 inhibited cell proliferation and promoted the sensitivity of chemotherapy drug, Cisplatin(DDP) and Paclitaxel (TAXOL), in MCF-7 cells.Additionally, ESRP2 knockdown obstructed the cell cycle at the G1 phase and caused a decrease in cyclinD1 protein expression. These findings reveal that ESRP2 is highly expressed in breast cancer and is correlated with poor prognosis in breast cancer patients. ESRP2 knockdown can inhibit MCF-7 cell proliferation by arresting the cell cycle at the G1 phase and promoting the sensitivity of chemotherapy drugs (DDP and TAXOL)in MCF-7 cells. ESRP2 may be required for the regulation of breast cancer progression, as well as a critical target for the clinical treatment of breast cancer.